PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS MACROMEDIA FLASH 8 PADA MATA PELAJARAN TIK - Sakti, Andika Dwi; Putra, Yogi Irdes; Sabir, Arisman; Fitria, Desi (Information Technology Education Department, 2024)
This research focuses on the development of interactive learning media using Macromedia Flash 8, which is not only proven to be valid, practical, and effective, but also aims to improve the quality of ICT learning for grade X students at MAN 3 Bungo. Using the Research and Development (R&D) method and the 4D development model, this study successfully designed an interactive learning media that reached a validity level of 79.44%, with media, material, and language aspects met. In addition, teacher and student responses to the practicality of this media reached a high percentage, namely 93.86% and 88.22%. The effectiveness test results showed that the classical test results had reached 85%, exceeding the set KKM. Overall, it can be concluded that this learning media is a relevant and effective innovation in improving ICT learning, with positive implications for future learning media development.